Opportunities for immunotherapy in microsatellite instable colorectal cancer - Harm Westdorp; Felix L. Fennemann; Robbert D.A. Weren; Tanya M. Bisseling; Marjolijn J. L. Ligtenberg; Carl G. Figdor; Gerty Schreibelt; Nicoline Hoogerbrugge; Florian Wimmers; I. Jolanda M. de Vries (2016)
Microsatellite instability (MSI), the somatic accumulation of length variations in repetitive DNA sequences called microsatellites, is frequently observed in both hereditary and sporadic colorectal cancer (CRC). It has been established that defects in the DNA mismatch repair (MMR) pathway underlie the development of MSI in CRC. After the inactivation of the DNA MMR pathway, misincorporations, insertions and deletions introduced by DNA polymerase slippage are not properly recognized and corrected. Specific genomic regions, including microsatellites, are more prone for DNA polymerase slippage and, therefore, more susceptible for the introduction of these mutations if the DNA MMR capacity is lost. Some of these susceptible genomic regions are located within the coding regions of genes. Insertions and deletions in these regions may alter their reading frame, potentially resulting in the transcription and translation of frameshift peptides with c-terminally altered amino acid sequences. These frameshift peptides are called neoantigens and are highly immunogenic, which explains the enhanced immunogenicity of MSI CRC. Neoantigens contribute to increased infiltration of tumor tissue with activated neoantigen-specific cytotoxic T lymphocytes, a hallmark of MSI tumors. Currently, neoantigen-based vaccination is being studied in a clinical trial for Lynch syndrome and in a trial for sporadic MSI CRC of advanced stage. In this Focussed Research Review, we summarize current knowledge on molecular mechanisms and address immunological features of tumors with MSI. Finally, we describe their implications for immunotherapeutic approaches and provide an outlook on next-generation immunotherapy involving neoantigens and combinatorial therapies in the setting of MSI CRC.